2017
DOI: 10.1039/c7ra01845b
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium carbosilane dendrimers for biomedical applications – synthesis, characterization and cytotoxicity evaluation

Abstract: Phosphonium carbosilane dendrimers could represent an alternative to ammonium ones in gene therapy applications with high potential of mitochondrial targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…For this study, the dendrimers previously prepared in our group were used. Several batches of each dendrimer type differing by purity were usually obtained in the course of the synthetic sequence optimization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this study, the dendrimers previously prepared in our group were used. Several batches of each dendrimer type differing by purity were usually obtained in the course of the synthetic sequence optimization.…”
Section: Methodsmentioning
confidence: 99%
“…1D NMR spectra of all studied dendrimers were reported previously . The structures of products and the peak assignment were confirmed by gCOSY.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in Table , all the amphiphilic compounds only marginally affected cell growth, since viability values were in the range 79.9–111.7% for B14 cells and 79.6–105.8% for BRL cells, and, even if not extravagantly, they were less cytotoxic than dendrimers H1 and H2 not equipped with the C‐18 chain. Furthermore the achieved amphiphilic dendrimers were found to be much less cytotoxic than PEI25K that at a concentration of 40 µg mL −1 determines the survival of only 30–40% of two cancer cell lines …”
Section: Resultsmentioning
confidence: 99%
“…(Rose et al, ) Phosphonium containing compounds are generally less toxic than their ammonium equivalents due to differences in ionic radius and charge distribution. (Rose et al, ; Stekar et al, ; Strasak et al, ) In addition, phosphonium based lipids have been shown to transfect cells with high efficacies and lower toxicity than ammonium analogues. (Guenin et al, ) Interestingly, the few polymeric phosphonium materials reported so far in the literature showed a similar trend in relation to toxicity.…”
Section: Introductionmentioning
confidence: 99%